2018
DOI: 10.1039/c8tx00009c
|View full text |Cite
|
Sign up to set email alerts
|

Individual heavy metal exposure and birth outcomes in Shenqiu county along the Huai River Basin in China

Abstract: : Exposure to heavy metals during pregnancy is an important risk factor for adverse birth outcomes. We aimed to investigate the current heavy metal exposure levels in cord blood from healthy pregnant women residing in the Huaihe River Basin, China, and examined the association between heavy metal levels and dietary habits and lifestyle factors. In this study, we measured the exposure levels of five heavy metals in the umbilical cord blood from 350 healthy pregnant women and administered 350 self-reported quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…Another positive and signi cant correlation was observed between Pb and Cd levels in the maternal blood and the umbilical cord blood. These results are consistent with the studies of Lin et al 2018(Lin et al 2018). The presence of Se in maternal blood prevents many toxins from entering to the fetus(Magos et al 1980).…”
supporting
confidence: 94%
See 1 more Smart Citation
“…Another positive and signi cant correlation was observed between Pb and Cd levels in the maternal blood and the umbilical cord blood. These results are consistent with the studies of Lin et al 2018(Lin et al 2018). The presence of Se in maternal blood prevents many toxins from entering to the fetus(Magos et al 1980).…”
supporting
confidence: 94%
“…The results of our study showed that 78.48%, 73.81% and 39.29% of pregnant women and 83.53%, 43.53%, and 80% of the umbilical cord samples were below the recommendations of CDC levels for Pb, Cd, and As, respectively. While 21.52%, 26.19%, and 60.71% of maternal blood samples and 16.47%, 56.47%, and 20% of umbilical blood samples were higher than the CDC recommended levels for Pb, Cd and As, respectively.The presence of toxic metals even at low concentrations in the blood of pregnant women can also damage the fetus(Ha et al 2009;Lin et al 2018). Job-related contacts and foods are effective factors in exposure to toxic metals (Martí-Cid et al2008).Studies have revealed that approximately 88% of rice consumed in Iran (including Iranian, Pakistani, and Indian brands) does not meet national standards and WHO/FAO guidelines, and the health risks are unacceptable(Shara et al 2019).…”
mentioning
confidence: 99%
“…More seriously, the transfer of HMs from soil to cereals and plants is a major HM intake route for humans. Excessive HMs may accumulate in specific human organs and interact with proteins and enzymes, making them damaged or inactive [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Хронические эффекты мышьяка выражаются в поражении кожи, нейротоксичности, сердечнососудистых заболеваниях, диабете и раке. Международным агентством исследований рака (IARC) мышьяк и его неорганические соединения классифицируется как Carcinogenic to Humans (группа I) (IARC, 1980 [17] Геометрические средние уровня мышьяка в пуповинной крови рожениц -0,92 ± 1,01 нг/мл при 0,43 ± 0,88 нг/мл (n = 296) у здоровых младенцев [19]. При пероральном однократном воздействии мышьяковистого ангидрида в дозе 30 мг/кг установлено торможение процесса элиминации мышьяка из организма, что совпадает с порогом острого действия мышьяковистого ангидрида по изменению содержания SH-групп крови 4 В организме кур, получающих мышьяк с кормом в дозе 0,5-5,0 мг/кг, содержание мышьяка в мышечной ткани составляло 0,11-0,20 мг/кг, в печени -0,09-0,12 мг/кг, в почках -0,09-0,34 мг/кг и в яйцах -0,12-0,24 мг/кг 5 .…”
unclassified